Prevalence and molecular epidemiology of carbapenem resistance in Asia: a systematic review and meta-analysis - Nishadi Jayathilaka; Sashini Shehana; Dilini Nakkawita; Thamarasi Senaratne (Systematic Reviews)
Abstract Background Carbapenems are a group of last-resort antibiotics used to treat serious life-threatening infections. The emergence of resistance to carbapenems is a major public health threat. However, comprehensive information on the prevalence and molecular epidemiology of carbapenem resistance (CR) among Asian countries is lacking. Therefore, we aimed to determine the prevalence of CR and associated molecular determinants quantitatively among Asian countries. Methods In this systematic review and meta-analysis, we searched published reports in electronic databases such as PubMed, ScienceDirect, the Cochrane Library, and Web of Science from 1st of January 2014 to 31st of January 2024 that fulfilled these criteria; original studies conducted in Asian countries including clinical isolates, and published in English. Data extraction and risk-of-bias assessment were performed by two independent reviewers. The pooled prevalence of CR with 95% confidence interval (CI) was computed with a random effects model. Heterogeneity across studies was determined by I 2. The geographical location, income level, publication year, and sample size were analyzed as subgroups. Results We identified 2518 eligible studies, of which 37 assessed the CR prevalence data of 10,433 patients. The pooled prevalence (PPr) of CR was 31.3% (95% CI: 0.22 to 0.40; I 2 = 99.9%; P = 0.00). A trend of CR incidence was observed from 2004 to 2023, with PPr values ranging from 7.4% to 50.6%. A variation in the distribution of CR genes was observed, with bla NDM being the most common gene, followed by bla OXA and bla KPC. Univariate meta-regression analysis indicated that geographical location, income level, publication year, and sample size did not significantly affect heterogeneity (P < 0.05). Conclusion The results suggest that surveillance of CR among Asian countries is essential to reduce the burden of antibiotic resistance. Mitigating the impact of CR infections will safeguard the efficacy of carbapenems for future generations and reduce further dissemination of CR genes. Systematic review registration PROSPERO CRD42024515806.